Human Blood Tissue Intrinsic Bioelectromagnetic Energy Transferring Onto a Miniorgan - A. Embí, Abrahám (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
Basically, the human hair consists of a follicle a.k.a root penetrating the skin and an outer skin structure commonly called the shaft. The hair follicle has been classified as a miniorgan having its own cells divisions; aging stages and also demonstrated to emit electromagnetic radiation. The intent of this manuscript is to demonstrate via in vitro experiments evidence of human inter-tissue electromagnetic energy transfer through a glass slide, namely from human blood tissue to the previously described miniorgan or follicle. The intrinsic biomagnetism of organs such as the brain and heart have been found to emit bioelectrical signals that could presently be displayed by instrumentation. The mechanism behind this new finding was possible due to the introduction in 2015 of a tabletop optical microscopy method designed to display plants and animal tissue electromagnetic energy emissions. Essential to present finding is the described property of anisotropic crystals of full absorption of incoming electromagnetic radiation waves by Potassium Ferricyanide (K3Fe) which is an anisotropic crystal is an anisotropic crystal. For example, a single layer human blood smear was sandwiched (SDW) by a second glass slide. On the top slide of the SDW, a freshly plucked in toto human hair was then covered by drops diluted K3Fe. Control experiments had repeatedly shown orderly semicircular periodic crystals of K3Fe triggered by the electromagnetic waves emitted by the hair follicle. Prior experiments by this author, have hinted at a “bioelectromagnetic cross-talk” between the follicle and blood. This was seen when there was physical contact between the follicle and blood drops on a glass slide. In the present experiments there is no direct tissue contact, the blood tissue energy is transmitted through a 1 mm glass barrier. The data herein presented introduces Bioelectromagnetic Fields (BEMFs) energy from human blood onto a miniorgan. This energy is shown penetrating a 1 mm glass slide barrier. Further research is warranted to assess the physiological implications of the human blood tissue as a molecular and BEMFs energy source.